EFFECTS OF BACTERIAL ENDOTOXINS ON METABOLISM : VI. THE ROLE OF TRYPTOPHAN PYRROLASE IN RESPONSE OF MICE TO ENDOTOXIN - Berry, L. Joe (The Rockefeller University Press, 1963)
Cortisone is known to protect mice against the lethal effects of endotoxin. It also elevates liver tryptophan pyrrolase (TP) activity, an enzyme that converts tryptophan into an intermediate which, in turn, is transformed in a series of reactions into nicotinamide, a component of the pyridine nucleotides. In the present report, results of experiments attempting to link the prophylactic action of cortisone in endointoxication to metabolism of tryptophan are described. It was shown first that both nicotinamide and diphosphopyridine nucleotide (DPN), compounds along the pathway initiated by TP, are each as effective as cortisone in protecting mice against lethality of different amounts of endotoxin. L-Tryptophan, which alone results in an increase in liver TP, fails to protect against endotoxin when it is given either 4 hours before or concurrently with the toxin while it potentiates the toxin when administered 4 hours later. Cortisone, nicotinamide, and DPN all fail to protect mice against lethality when given 4 hours after endotoxin but they do not potentiate it as does tryptophan. Additional evidence linking tryptophan metabolism to endotoxin poisoning was derived from assays for TP. Activity of the enzyme in livers of mice 17 hours after injecting an LD(50) of endotoxin is less than one-half the control value. It remains below normal for 48 hours. In adrenalectomized mice, TP activity is about the same as in mice 17 hours after endotoxin. Animals protected against lethality of endotoxin by cortisone have normal levels of TP but if the cortisone is given 4 hours after the toxin, TP activity is the same as in mice given endotoxin alone. Tryptophan is unable to maintain a normal level of TP when it is given concurrently with endotoxin. TP activity is not depressed when mice made tolerant to endotoxin are given an injection of endotoxin at the LD(50) level for normal animals. Normal activity of the enzyme was always observed in livers of mice protected against endotoxin but not in those where protection failed. The total amount of oxidized pyridine nucleotides (PN(+)) in livers of mice 17 hours after an LD(60) of endotoxin is about two-thirds the normal level. Animals injected with either cortisone or nicotinamide at the same time as endotoxin maintain the PN(+) level in liver. Mice exposed to 5°C during the postinjection period can be protected with cortisone or nicotinamide against lethality of endotoxin but not with DPN. Changes in TP activity do not parallel those found in mice kept at 25°C. The toxic manifestations of endotoxin appear to be different, therefore, in animals stressed by cold.